Enzymatic Synthesis and Characterization of Biodegradable Poly(w-pentadecalactone-co-e-caprolactone) Copolymers - Cansu Ulker*; Yuksel Guvenilir (Journal of Renewable Materials, 2018)
As an alternative biodegradable aliphatic polyester, poly(w-pentadecalactone-co-ε-caprolactone) copolymer was synthesized via enzymatic ring-opening polymerization. A new biocatalyst, Candida antarctica lipase B, immobilized onto rice husk ash was used for catalysis. Reactions were carried out at various temperatures and periods for varied copolymer compositions in order to obtain the highest molecular weight copolymer. The best reaction parameters were found to be 80 °C and 6 hours and molecular weights increased proportionally with the amount of w-pentadecalactone (w-PDL). The molecular structure of copolymer with 75% weight ratio of w-PDL (Mn = 19720 g/mol) was characterized by proton and carbon nuclear magnetic resonance spectroscopies (1H-NMR and 13C-NMR). Thermal properties of the same copolymer and homopolymers were investigated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Improved thermal features were shown by addition of w-PDL to the structure and compared with poly(ε-caprolactone) (PCL). Consequently, poly(w-pentadecalactone-co-ε-caprolactone) copolymers were found to be good alternatives to widely used polyester, PCL, with their rapid polymerization tendency, higher molecular weights, and improved thermal features.